Rola i zadania kierownika liniowego w procesie coachingu pracowników - Janiak-Rejno, Iwona (The role and tasks of line Manager in the employee's coaching process, 2007)
Coaching is an informal training technique with a wide range of the potential advantages. Coaching creates a direct relation between coach and employee. The line manager has both a very essential and difficult task in this process. He represents two different roles, he is both employees’ coach/trainer and their superior. Coaching effectiveness depends on three main factors. They are manager’s ability to integrate these two roles, the ability to match ways and forms of coaching i mplementation and level manager’s competencies. The paper presents the role, the key tasks, and the essential principles which could be useful for line manager in the coaching process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Zarządzanie (5); 2007; nr 1187, s. 213-224